Characterization of fish protein hydrolysate from tilapia (Oreochromis niloticus) by-product - Roslan, Jumardi; Md. Yunos, Khairul Faezah; Abdullah, Norhafizah; Mustapa Kamal, Siti Mazlina (Elsevier, 2014)
Several by-products, such as skin, bones, frames, heads and tails are produced during the processing of tilapia fish (Oreochromis niloticus) into fillets. These by-products can be converted into tilapia by-producthydrolysate powder(TBHP) with beneficial functional properties. The TB hydrolysate produced through enzymatic hydrolysis was characterized in term of chemical and amino acid (AA) compositions, molecular weight distribution and ACE inhibition activity. TBHP has showna good nutritional value with high protein content (62.71%)and essential amino acids (199.15 mg/g).High value of ACE inhibition activity (88.26%) in TBHP might be due to the presence of low molecular weight peptides.